Expression of surface markers on peripheral CD4＋CD25^high T cells in patients with atopic asthma： role of inhaled corticosteroid - ZHANG Qian QIAN Fen-hong LIU Hua ZHOU Lin-fu HUANG Mao ZHANG Xi-long YIN Kai-sheng (Chinese medical journal, 2008)
Background CD4^＋CD25^＋ regulatory T cells （Tregs） mediate immune suppression through cell-cell contact with surface molecules, particularly cytotoxic T lymphocyte-associated antigen 4 （CTLA-4）, glucocorticoid-induced tumor necrosis factor receptor family-related protein （GITR）, and transforming growth factor β （TGF-β）, but little is known about the exact role of Tregs in the pathogenesis of asthma. This study sought to characterize the expression of surface markers on peripheral blood mononuclear cells-derived Tregs in patients with atopic asthma and healthy subjects, and to investigate the effect of inhaled corticosteroid on them. Methods The expression of surface molecules on CD4^＋CD25^high Tregs was detected by flow cytometry. The effect of inhaled corticosteroid on expression of the surface molecules on Tregs was determined in vivo and in vitro. Total serum immunoglobulin E （IgE） and high-sensitivity C-reactive protein were measured by enzyme linked immunosorbent assay and latex enhanced immunoturbidimetric assay, respectively. Results Equivalent numbers of peripheral Tregs were found in patients with atopic asthma （stable and acute） and healthy subjects. Tregs preferentially expressed CTLA-4, GITR, toll-like receptor 4 （TLR4）, latency-associated peptide （LAP/FGF-β1）, and forkhead box P3 （FOXP3）. Patients with acute asthma had decreased numbers of CD4^＋CD25^highLAP^＋ T cells compared to healthy subjects and stable asthmatics. Inhaled corticosteroid enhanced the percentage of Tregs expressing LAP in vivo and in vitro dose-dependently. Furthermore, the percentages of Tregs expressing LAP were negatively correlated with total serum IgE levels and severity of asthma, but positively correlated with forced expiratory volume in one second percentage of the predicted value in patients with asthma. Conclusions The results suggest that membrane-bound TGF-β1 is a potential candidate for predicting the severity of asthma, and may contribute to the sustained remission of asthma. Strategies targeting Tregs on their surface markers, especially TGF-β1, are promising for future therapy of asthma.